Effects of International Migration on Destination and Source Countries (Russia-Central Asia Example) - Ergeshkyzy, Aziza (Scientific Journal of Faculty of Theology, 2023)
In every period of history, poverty, natural disasters, wars and conflicts in various regions of the world have been among the reasons that forced people to migrate to other regions. This mobility, the participation of which is increasing day by day, creates many positive and negative consequences by directly and indirectly affecting both the source and target country, society and individual. According to experts, in terms of socio-economic consequences of the migration flow from abroad for the destination country, it is suggested that it will have positive results such as eliminating the employment gap of migrant workers in the country, growing economic indicators in many sectors of the economy and contributing to the budget, while it will reduce unemployment and increase foreign exchange inflows for the source country. In addition, migration has negative aspects for both countries. In this context, it is also a fact that a significant portion of international immigrants do not pay taxes because they are employed in the shadow sector of the economy, negatively affecting the financial conditions of the receiving country. Contrary to these negative approaches, the demographic crisis in Russia has been greatly alleviated by immigrants from Central Asian lands, vacant positions that are not prestigious and undemanded for the local people have been filled by these immigrants, contributing to the development of the service sector, and since most of the immigrant workers work illegally, cheap labor has been provided. Situations such as this provide great profits to the target country. From the perspective of the source country, the departure of qualified experts from the country leads to the deterioration of the intellectual potential in science, the mass migration of the young population of working age leads to demographic problems in the source country, the disintegration of families, and the increase of street children. On the other hand, immigrants can improve their skills, general education and cultural levels while abroad, help the formation of a middle class in the source country by establishing small and medium-sized businesses after returning to their country, increase the living standards of the society with the income they earn, establish business connections in the country where they live as immigrants, and collaborate in areas such as trade and production. Addressing these ongoing impacts in a multifaceted manner will enable a better understanding of the consequences of migration and resolution of the problems arising due to migration.